2017
DOI: 10.1111/jvim.14901
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Plasma Cell‐Free DNA and Creatine Kinase in a Canine Model of Tissue Injury

Abstract: BackgroundCell‐free DNA (cfDNA) comprises short, double‐stranded circulating DNA sequences released from damaged cells. In people, cfDNA concentrations correlate well with disease severity and tissue damage. No reports are available regarding cfDNA kinetics in dogs.Objectives/HypothesisCell‐free DNA will have a short biological half‐life and would be able to stratify mild, moderate, and severe tissue injury. Our study aims were to determine the kinetics and biological half‐life of cfDNA and to contrast them wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Among these contents are fragments of DNA, known as "cell-free DNA" once they have left the confines of the cell and its nucleus. These cfDNA fragments are rapidly degraded by normal metabolic processes and have a very short half-life, estimated at 15 min to a few hours in both humans and dogs; as a result, they are usually cleared within a few days (168)(169)(170). The constant turnover of cells throughout the body provides a steady supply of cfDNA in the circulation, which is amenable to analysis with sophisticated technologies including NGS.…”
Section: Cfdna Origins and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these contents are fragments of DNA, known as "cell-free DNA" once they have left the confines of the cell and its nucleus. These cfDNA fragments are rapidly degraded by normal metabolic processes and have a very short half-life, estimated at 15 min to a few hours in both humans and dogs; as a result, they are usually cleared within a few days (168)(169)(170). The constant turnover of cells throughout the body provides a steady supply of cfDNA in the circulation, which is amenable to analysis with sophisticated technologies including NGS.…”
Section: Cfdna Origins and Characteristicsmentioning
confidence: 99%
“…Published research on canine cfDNA has covered a variety of clinical applications, including trauma, sepsis, thromboembolism, and neoplasia, and has focused primarily on determining the concentration of cfDNA in plasma as correlated to a particular clinical state or as a predictor for certain clinical outcomes ( 84 , 148 151 , 167 , 169 , 191 203 ). Studies that evaluated cfDNA concentrations in healthy canine subjects have reported median concentrations ranging from less than 1 ng/mL to greater than 500 ng/mL ( 148 , 149 , 167 , 169 , 194 203 )—significantly wider than the range documented in healthy humans (typically 0–20 ng/mL) ( 204 ). These wide-ranging findings suggest that additional research employing well-controlled, large-scale studies is required to better understand the fundamental characteristics of cfDNA in dogs; they also point to the need for standardized, reproducible methods for blood collection, extraction, and measurement of canine cfDNA.…”
Section: Liquid Biopsy: the Next Frontier In Veterinary Cancer Carementioning
confidence: 99%
“…33,34 Elevated cfDNA might also reflect physiological (e.g., exercise) 35,36 and non-malignant pathological processes, 7 such as inflammation, diabetes, tissue trauma, sepsis, and myocardial infarction. [37][38][39] The concentration of cfDNA in blood varies significantly; it ranges between 0-5 and >1000 ng/ml in patients with cancer and between 0 and 100 ng/ml in healthy subjects. 7,24 There is also a marked variation in blood ctDNA levels among patients with different tumor types.…”
Section: Introductionmentioning
confidence: 99%
“…In veterinary medicine, cfDNA has recently gained attention and more particularly in dogs. As in human medicine, it has been found that cfDNA has a short half-life in canine plasma (around 5 hours) 15 and its concentration is increased in various diseases such as immune-mediated hemolytic anemia 16 , sepsis, severe trauma or inflammation [17][18][19] . In dogs, cfDNA concentration is also correlated with the severity of the disease and prognosis 18 .…”
Section: Introductionmentioning
confidence: 99%